ISLAMIC INSURANCE IN INDONESIA: OPPORTUNITIES AND CHALLENGES ON DEVELOPING THE INDUSTRY - Maf’ula, Faricha; Mi’raj, Denizar Abdurrahman (Universitas Muhammadiyah Surakarta, 2022)
Islamic insurance is a minor industry compared with other Islamic financial institutions in Indonesia. However, it has enormous potential to grow together with its challenges. This study aims to analyze the opportunities and challenges of the Islamic insurance industry in Indonesia. This research uses a qualitative methodology to describe the nature of reality. The result summarizes that the possibilities are: domino effect from Halal Value Chain and other development of government-owned enterprises; digitalization in Islamic Finance; and potential market of micro takaful. The challenges are needing a set regulatory framework as a catalyst to force supply and demand; market penetration is low, issues of Islamization insurance and the inadequate development of Islamic insurance products, limited retakaful company and qard hassan fund issue in retakaful.